Political power and social theory - Go, Julian, 1970- (Bingley, U.K. : Emerald, 2012)
As economic stagnation freezes the globe; capitalism is increasingly questioned; war, revolution and political instability unsettles the Middle East; and President Obamas campaign for the Presidency looms, Volume 23 of Political Power and Social Theory reflects on these and related issues. Chapters in this volume discuss the meaning of revolution, the origins of neoliberalism in India, identity formation in a Chicago social movement, the Palestinian National Question, and the Black middle-class in the US. Additionally, in the Scholarly Controversy section, Fred Block questions whether the concept of "capitalism" should be problematized entirely.
Free riding on revolution : conservatism and social change / Robin Archer -- Parties and the articulation of neoliberalism : from "the emergency" to reforms in India, 1975-1991 / Manali Desai -- "A new health order as part of the new social order" : the strategic response of the WHO to its member states / Nitsan Chorev -- The reconfiguration of the Palestinian national question : the indirect rule route and the civil society route / Silvia Pasquetti -- Transforming citizenship : the subjective consequences of local political mobilization / Rachel Meyer -- Political fields and religious movements : the exclusion of the Ahmadiyya community in Pakistan / Sadia Saeed -- Racialized class formation : blacks in the professional middle class in the post-civil rights era / Eric S. Brown -- Varieties of what? : should we still be using the concept of capitalism? / Fred Block -- A Polanyian analysis of capitalism : a commentary on Fred Block / Nina Bandelj -- Marx, Weber, and the "ceaseless accumulation of capital" / Ho-Fung Hung -- On Fred Block, varieties of what? : should we still be using the concept of capitalism? / Wolfgang Streeck -- There was no baby in this bathwater : a reply to the critics / Fred Block.
Print version record
Keywords: Political Science -- Political Process -- General; Political Science -- Public Policy -- Social Policy; Political science & theory; Society & culture: general; Power (Social sciences); Political sociology; Social sciences -- Philosophy